TREM2 deficiency exacerbates cognitive impairment by aggravating α-Synuclein-induced lysosomal dysfunction in Parkinson’s disease - Baoyu Zhu; Jiezhu Feng; Xiaomei Liang; Zhongling Fu; Mengshi Liao; Tongtong Deng; Kaicheng Wang; Jianwei Xie; Jieshan Chi; Lu Yang; Yuyuan Gao; Kun Nie; et al. (Cell Death Discovery)
Abstract Cognitive impairment in Parkinson’s disease (PD) is a widespread and rapidly progressive feature that impacts prognosis. Although TREM2 has been implicated in neuroprotection across various neurodegenerative diseases, its specific role in PD remains to be clarified. In this study, we first detected the hippocampus of human PD specimens and of the mutant A53T α-Synuclein transgenic mice (A53T mice), and found a significant increase in the number of TREM2+ microglia. To evaluate the effects of TREM2 deficiency, TREM2-deficient A53T mice (TREM2-/-/A53T mice) were generated. In these mice, exacerbated cognitive impairment, neurodegeneration, disruption of synaptic plasticity, and accumulation of pathological α-Synuclein (α-Syn) in the hippocampus were observed, without any detected motor dysfunction. Despite increased infiltration of activated microglia surrounding α-Syn aggregates, lysosomal dysfunction in microglia was aggravated in the TREM2-/-/A53T mice. In addition, transcriptional analyses and in vitro experiments further found that TREM2 knockdown inhibited the nuclear distribution of TFEB via the ERK1/2 pathway, exacerbating α-Syn-induced lysosomal dysfunction and causing more pathological α-Syn accumulation. Finally, HT22 cells were cocultured with TREM2 knockdown of BV-2 cells pretreated with recombinant human A53T α-Syn preformed fibrils (PFFs). The coculture experiments showed that TREM2 knockdown in BV-2 cells pretreated with PFFs enhanced the phosphorylation of α-Syn and promoted apoptosis in HT22 cells via inhibiting α-Syn degradation. In conclusion, TREM2 deficiency exacerbates cognitive impairment in PD by exacerbating α-Syn-induced microglial lysosomal dysfunction, identifying TREM2 as a potential therapeutic target.